2016
DOI: 10.1120/jacmp.v17i1.5701
|View full text |Cite
|
Sign up to set email alerts
|

Radiation intensity () and visibility of anatomical structures in head CT examinations

Abstract: The purpose of this study was to quantify how changing the amount of radiation used to perform routine head CT examinations (CTDIvol) affects visibility of key anatomical structures. Eight routine noncontrast head CT exams were selected from six CT scanners, each of which had a different CTDIvol setting (60 to 75 mGy). All exams were normal and two slices were selected for evaluation, one at the level of basal ganglia and the other at the fourth ventricle. Three experienced neuroradiologists evaluated the visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…This finding indicated that the protocol for head CT examination produces too high a dose and too low noise, the dose could be further reduced while maintaining diagnostic image quality. Previously, Tipnis et al [42] reported that a decrease in output dose from 75 to 60 mGy in head CT examinations produced no clear degradations in depicting neuroanatomy. Based on this finding, the noise in the head image could be further increased up to about 5 HU which may be obtained with a dose lower than 60 mGy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicated that the protocol for head CT examination produces too high a dose and too low noise, the dose could be further reduced while maintaining diagnostic image quality. Previously, Tipnis et al [42] reported that a decrease in output dose from 75 to 60 mGy in head CT examinations produced no clear degradations in depicting neuroanatomy. Based on this finding, the noise in the head image could be further increased up to about 5 HU which may be obtained with a dose lower than 60 mGy.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, however, the calculated noise level has not been compared with visual observations by expert radiologists [42]. In a follow-up study, we will compare quantitative noise levels from automated methods with qualitative radiological observations determined by a radiologist.…”
Section: Discussionmentioning
confidence: 99%